2010
DOI: 10.1093/toxsci/kfq096
|View full text |Cite
|
Sign up to set email alerts
|

3-Methylcholanthrene Induces Differential Recruitment of Aryl Hydrocarbon Receptor to Human Promoters

Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated protein that mediates the toxic actions of polycyclic aromatic and halogenated compounds. Identifying genes directly regulated by AHR is important in understanding the pathways regulated by this receptor. Here we used the techniques of chromatin immunoprecipitation and DNA microarrays (ChIP-chip) to detect AHR-bound genomic regions after 3-methylcholanthrene (3MC) treatment of T-47D human breast cancer cells. We identified 241 AHR-3MC-bound regions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
6
26
0
Order By: Relevance
“…Of note, AhR has been shown to be recruited to the XRE-like sequence (AhRE II) in some AhR-inducible genes (Boutros et al, 2004;Sogawa et al, 2004), and most recently a nonconventional, Arnt-independent XRE was defined (Huang and Elferink, 2012). Furthermore, in agreement with the above reports, genome-wide ChIP-on-chip studies suggested that a large proportion of the AhR binding sequences did not harbor canonical XREs (Ahmed et al, 2009;Pansoy et al, 2010).…”
Section: Xenobiotic and Suspension Activation Of Ahr 1089supporting
confidence: 69%
“…Of note, AhR has been shown to be recruited to the XRE-like sequence (AhRE II) in some AhR-inducible genes (Boutros et al, 2004;Sogawa et al, 2004), and most recently a nonconventional, Arnt-independent XRE was defined (Huang and Elferink, 2012). Furthermore, in agreement with the above reports, genome-wide ChIP-on-chip studies suggested that a large proportion of the AhR binding sequences did not harbor canonical XREs (Ahmed et al, 2009;Pansoy et al, 2010).…”
Section: Xenobiotic and Suspension Activation Of Ahr 1089supporting
confidence: 69%
“…Previously reported ChIP-chip data from our laboratory revealed that in both human cells and mouse tissue, FKH sites are significantly enriched in AHR-bound regions supporting a possible role for forkhead proteins in AHR signaling (8,9,46). In support of these data, we show that FOXA1 is critical for the AHR-dependent induction of CCNG2 levels.…”
Section: Discussionsupporting
confidence: 86%
“…Wellstudied AHR target genes include the phase I and II drug-metabolizing enzymes, such as cytochrome P450 1A1 (CYP1A1), CYP1B1, and glutathione S-transferases. Chromatin immunoprecipitation combined with microarrays (ChIP-chip) and gene expression microarray experiments revealed that AHR regulates numerous genes involved in diverse cellular pathways, including metabolism and cellcycle regulation (8)(9)(10). In support of these findings, previous studies have shown that TCDD inhibits cell proliferation (11)(12)(13).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The parent MC molecule binds AHR with relatively high affinity (Riddick et al 1994) and alters expression of numerous AHR target genes (Kondraganti et al 2005;Pansoy et al 2010); however, studies with MC are complicated by time-dependent changes in biological potency caused by its rapid biotransformation to multiple metabolites (Poland and Glover 1974;Riddick et al 1994), some of which are highly reactive and toxic (Mathieu et al 2001). In contrast, TCDD is highly resistant to biotransformation and causes persistent AHR activation without being converted to reactive metabolites in the process, providing an opportunity for a cleaner assessment of the importance of AHR activation per se in a given biological response.…”
Section: Introductionmentioning
confidence: 99%